Academic Entrepreneurship in the Czech Republic - Tetřevová, Liběna; Vlčková, Vladimíra (Slovak Academic Press Ltd, 2019)
Other than financial and non-financial effects for universities, academic entrepreneurship also generates new thoughts and ideas and allows for transfer of knowledge, leading to creation of inventions and innovations. Thanks to this, academic entrepreneurship represents a source of economic growth and competitiveness and contributes significantly towards sustainable development. This role appears to be especially important from the point of view of post-communist economies which are still to a certain extent transforming. The objective in this study is therefore to assess the level of academic entrepreneurship in one of the post-communist countries – a small economy with a traditional role played by education – the Czech Republic. Data gained via a questionnaire survey, the respondents of which were competent managers from 76 HEIs and faculties working in the Czech Republic, was compared with the relevant international studies.
Akademické podnikání v České republice
Keywords: academic entrepreneurship; higher education institution; knowledge transfer; Czech Republic; akademické podnikání; vysoká škola; transfer znalostí; Česká republika